Muistitietotutkimuksen paikka Teoriat, käytännöt ja muutos - Savolainen, Ulla; Taavetti, Riikka (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2022)
The volume is a comprehensive handbook of oral history and memory studies in Finland. The Finnish research field has originally emerged at the collaborative intersection of history, folklore studies, and ethnology. Since then, this field has developed into vibrant multi- and cross-disciplinary arena characterized by a strong focus on methodological issues related to memory in culture and theoretical engagement with studies on narration and processes of remembering. The chapters of the book explore the perspectives on the production of memory-based knowledge in oral history interviews and collection campaigns of written reminiscences. Moreover, the book introduces versatile methodological approaches to the study of memory and memories, ranging from narrative to corpus analysis, and investigates the multiple media of remembrance from documentary film to museum exhibition. The chapters of the book also engage the field's disciplinary position and interrogate the potentials and challenges related to the application of the methods of oral history research and the use of memory-based knowledge beyond academia in political, societal, and community-based projects.